Division of Complex Numbers

We at ask-math believe that educational material should be free for everyone. Please use the content of this website for in-depth understanding of the concepts. Additionally, we have created and posted videos on our youtube.

We also offer One to One / Group Tutoring sessions / Homework help for Mathematics from Grade 4th to 12th for algebra, geometry, trigonometry, pre-calculus, and calculus for US, UK, Europe, South east Asia and UAE students.

Affiliations with Schools & Educational institutions are also welcome.

Please reach out to us on [email protected] / Whatsapp +919998367796 / Skype id: anitagovilkar.abhijit

We will be happy to post videos as per your requirements also. Do write to us.

Division of complex numbers : We know that for any complex numbers z1 and z2 (≠0), there exists complex number z such that
z1 = z . z2
This number z is denoted by $\frac{z1}{z2}$ called the division of complex numbers z1 by z2(≠ 0). In fact, division of complex-numbers is the inverse operation of multiplication.

= $\frac{(ac+bd)}{c^{2} + d^{2}}+ \frac{(bc - ad)i}{c^{2} + d^{2}}$

Properties of division of Complex Numbers

Closure property: The division of two complex-numbers is , by definition , a complex number. Hence, the set of complex numbers is closed under division.

Commutative and associative properties are not true for division of complex-numbers.

Examples on division of complex-numbers

Divide the following :
1) (8 + i) ÷ (5-i)
Solution : $\frac{(8+i)}{(5-i)} $
( multiply numerator and denominator by the conjugate of denominator)
= $\frac{(8+i)}{(5-i)}\frac{(5+i)}{(5+i)}$

=$\frac{(40 +8i + 5i +i^{2})}{(25-i^{2})}$

=$\frac{(40 +13i -1)}{(25+1)}$

= $\frac{(39+ 13i)}{(26)}$

= $\frac{39}{26}+\frac{13i}{26}$

= $\frac{3}{2}+\frac{i}{2}$

2) Write the complex z = $\frac{(2 +i)}{(1+i)(1-2i))}$
Solution : We have, $\frac{(2 +i)}{(1+i)(1-2i))}$
=$\frac{(2 +i)}{(1 -2i +i -2i^{2})}$

= $\frac{(2 +i)}{(1 -i +2)}$

=$\frac{(2 +i)}{(3 - i )}$

= $\frac{(2 +i)(3+i)}{(3-i)(3 +i)}$

= $\frac{(6 +2i + 3i +i^{2})}{(9-i^{2})}$

=$\frac{(6 +5i -1)}{(9+1)}$

=$\frac{(5 +5i)}{(10)}$

=$\frac{1}{2}+ \frac{1}{2}i$ = x + iy

∴ x =$\frac{1}{2}$ and y = $\frac{1}{2}$

11th grade math

From Division of complex numbers to Home

Russia-Ukraine crisis update - 3rd Mar 2022

The UN General assembly voted at an emergency session to demand an immediate halt to Moscow's attack on Ukraine and withdrawal of Russian troops.